2004
DOI: 10.1007/s00520-003-0568-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: disease and nutrition are key determinants of patients? quality of life

Abstract: Although cancer stage was the major determinant of patients' QoL globally, there were some diagnoses for which the impact of nutritional deterioration combined with deficiencies in nutritional intake may be more important than the stage of the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(73 citation statements)
references
References 30 publications
3
66
0
1
Order By: Relevance
“…Previous studies have reported that weight loss is associated with a lower QoL. Weight loss has also been shown to be an important prognostic indicator of poor survival [6], and energy intake has been found to be correlated with symptoms including nausea, vomiting, and diarrhea [20]. This longitudinal study over 12 months included some patients with advanced stages of disease which not surprisingly resulted in significant attrition between T2 and T3.…”
Section: Study Strengths and Limitationsmentioning
confidence: 94%
“…Previous studies have reported that weight loss is associated with a lower QoL. Weight loss has also been shown to be an important prognostic indicator of poor survival [6], and energy intake has been found to be correlated with symptoms including nausea, vomiting, and diarrhea [20]. This longitudinal study over 12 months included some patients with advanced stages of disease which not surprisingly resulted in significant attrition between T2 and T3.…”
Section: Study Strengths and Limitationsmentioning
confidence: 94%
“…Several studies have shown that cachexia itself contributes to lower scores more so than tumor location, duration, or stage [17, 18]. Outward effects of cachexia include a decrease in physical activity and the ability to perform activities of daily living, which may play a role in a person's psychological well-being.…”
Section: Clinical Significance Of Cancer Cachexiamentioning
confidence: 99%
“…Malnutrition is observed in up to 80% of patients with advanced cancer [15]. Decreased dietary intake, cancer cachexia (characterized mainly by weight loss and muscle wasting), and nutrition impact symptoms may all contribute to cancer-related malnutrition [6].…”
Section: Introductionmentioning
confidence: 99%